2003
DOI: 10.1021/bm0257053
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogels for an Accommodating Intraocular Lens. An Explorative Study

Abstract: In this study it was investigated whether hydrogels could be used for an accommodating lens. The requirements of such a hydrogels are a low modulus, high refractive index, transparency, and strength. Since conventional hydrogels do not possess this combination of properties, a novel preparation method and new polymers are introduced. As starting materials poly(1-hydroxy-1,3-propanediyl), poly(ethylene-co-vinyl alcohol), poly(vinyl alcohol), and poly(allyl alcohol) were used. The first three were cross-linked w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Microsystems based on hydrogels are also being used in developing liquid lens systems that are capable of independently focusing [73,74,75]. The hydrogel polymers used in the manufacture of soft contact lenses are usually hydrophilic materials and hence expected to have a highly wettable surface, when fully hydrated.…”
Section: Synthetic Polymer Based Hydrogelsmentioning
confidence: 99%
“…Microsystems based on hydrogels are also being used in developing liquid lens systems that are capable of independently focusing [73,74,75]. The hydrogel polymers used in the manufacture of soft contact lenses are usually hydrophilic materials and hence expected to have a highly wettable surface, when fully hydrated.…”
Section: Synthetic Polymer Based Hydrogelsmentioning
confidence: 99%
“…Type B gelatin was dissolved in DMSO at 40–45 °C with stirring under nitrogen atmosphere for 6 h. Preliminary experiments showed that the addition of a small amount of 1,6‐diisocyanatohexane (HDI) to 5 or 10 wt.‐% gelatin solutions results in a sudden viscosity increase such that the mixtures could no be longer stirred and used to obtain films by solution casting. In order to overcome this problem, gelatin solutions and HDI were mixed directly in Petri dishes 10. 1,6‐Diisocyanatohexane was diluted in 2 mL of DMSO and poured in a PS Petri dish where 10 mL of the gelatin solution was promptly added.…”
Section: Experimental Partmentioning
confidence: 99%
“…8,9 The biocompatibility, flexibility, high transparency, high oxygen permeability and diffusivity in poly(2-hydroxyethyl methacrylate) (PHEMA) have made it the primary ingredient in soft contact lenses. 10 Other materials, such as poly(acrylate), poly(methacrylate), and poly(vinyl alcohol), 11,12 and self-assembled colloidal particles from poly(N-isopropylacrylamide-co-acrylic acid) 13 have also been studied. Most reported hydrogels lenses are, however, prepared from their corresponding liquid monomers by free radical polymerization, which makes them inappropriate for multi-beam interference lithography.…”
mentioning
confidence: 99%